Partisipasi Politik Pemuda dalam Pilkada Jawa Barat Tahun 2018 - Djuyandi, Yusa; Herdiansah, Ari Ganjar (Jurnal Bina Praja, 2018)
Pilkada is one of the means of democratic leadership succession in a country that claims to be a democracy. One indicator of the success of the democratic process, especially the elections, is the political participation of the community. Youth as an important segmentation in society also becomes important to be studied. This study aims to determine the level of youth participation in the West Java Provincial Election in 2018 and identify the factors driving youth political participation by using qualitative research methods. It is hoped that this research can be useful in improving the quality of Indonesian democracy in the future. The results of this study indicate that there are several factors that encourage an increase in youth political participation in the West Java Pilkad in 2018, namely the figure and track record of the candidate pairs, socialization and campaign factors, regional factors, ulama influence factors and political awareness of the community.